Construct validity of clinical nurse specialist core competency scale: An exploratory factor analysis. Issue 13 (4th May 2021) - Jokiniemi, Krista; Pietilä, Anna‐Maija; Mikkonen, Santtu
Abstract: Aim: To conduct a construct validity test on a clinical nurse specialist core competency scale. Background: Clinical nurse specialists' competency development dates back to the late 20th century; however, there is scarcity of competency descriptions from outside of North America. Furthermore, little knowledge is available on the previous research‐driven efforts to develop and validate clinical nurse specialist core competencies. Design: A descriptive study, using an online self‐report questionnaire, was conducted from May to September 2019 in three Nordic countries. Methods: An exploratory factor analysis using principal axis factoring and rotation method oblimin with Kaiser normalisation was undertaken to examine factors in the 50‐item scale. Parallel analysis with eigenvalue Monte Carlo simulation and scree plot was used to determine the number of factors to extract. Psychometric properties of the scale were evaluated, and subjective interpretation was used to modify the tool in line with the statistical analysis. The STROBE checklist was used as the reporting guideline for this study. Results: One hundred and eighty‐four responses were obtained (Finland n = 52, Denmark n = 95, Iceland n = 37) with an overall response rate of 45%. The results provided construct validity evidence of the underlying theoretical structures of the four competency spheres of patient, nursing, organisation and scholarship. Cronbach's alpha coefficient for the original overall scale was 0.94, thus indicating adequate reliability of the scale. Conclusions: Based on the analysis and subjective interpretation, we suggest a 47‐item clinical nurse specialist core competency scale. Further study should be conducted to validate the core competency content and construct in other contexts beyond the present study. Relevance to clinical practice: The scale may be used to guide clinical nurse specialist practice and identify areas for professional development, develop graduate‐level programme curricula and inform future competency research.